Biphasic activation of β-arrestin 1 upon interaction with a GPCR revealed by methyl-TROSY NMR - Yutaro Shiraishi; Yutaka Kofuku; Takumi Ueda; Shubhi Pandey; Hemlata Dwivedi-Agnihotri; Arun K. Shukla; Ichio Shimada (Nature Communications, 2021)
β-arrestins commonly bind to two distinct elements in GPCRs: the phosphorylated carboxyl terminal tail (C tail) and the cytoplasmic face of the transmembrane region (TM core). Here, the authors use methyl-TROSY NMR measurements to characterise the interactions between β-arrestin 1 (βarr1) and a GPCR and observe that C tail-mediated interaction with a GPCR alone induces the partial activation of βarr1, whereas the TM core- and C tail-mediated interactions together stabilize the activated conformation of βarr1.